The Effect of Red Betel Leaves (Piper Crocatum) Boiled Water On The Perineal Wounds Healing In Public Health Center Of Karangpawitan Of Garut Regency In 2021 - Indrayani, Triana; Rahmawati, Rani Septiani; Kurniati, Dewi (Universitas STRADA Indonesia, 2021)
Background: Based on the annual report of the Karangpawitan Health Center in 2020 there were 231 cases of postpartum women (29.3%) who experienced perineal injuries from 786 mothers who gave birth. In the first trimester of 2021, there were 56 cases of postpartum women (21.2%) who experienced perineal injuries from 263 women who gave birth. Meanwhile, cases of perineal wound infection in the first trimester of 2021 were 3 cases. Perineal wound care is expected to prevent infection, increase comfort and accelerate healing.Purpose: This study aimed to determine the effect of giving boiled red betel leaf water on perineal wound healing at the Karangpawitan Health Center, Garut Regency.Methods: This study was a quasi-experimental pretest posttest with control group design. The population in this study was 44 pregnant women in June 2021 who were divided into two groups, 22 experimental people and 22 controls, the sample technique used total sampling. The instrument used was a wound measurement questionnaire with the REEDA scale. Data analysis using Wilcoxon test.Results: the average perineal wound healing in the control group before the intervention was 6.86 and after the intervention was 1.86. While the experimental group before the intervention was 6.95 and after the intervention was 0.64. Bivariate results showed a p-value of 0.000 <0.05, meaning that there was an effect of using boiled red betel leaf water on perineal wound healing.Conclusion: There was an effect of using boiled red betel leaf water on perineal wound healing